Features of the Internal Position of a Parent in Primary School-Age Children - Galina G. Filippova; Svetlana A. Abdullina (Rossijskij psihologičeskij žurnal., 2016)
The paper examines the formation of the bases of the internal position of a parent in primary school-age children. The person’s internal position of a parent appears long before the birth of his/her own children; its components are formed in ontogenesis in accordance with the stages of the development of the parental sphere of personality. This study attempts the following: to disringuish components of the internal position of a parent; to explain the content of these components concerning primary school age; to define the criteria of the formation of the components of the primary internal position of a parent in primary school children; to examine the factors influencing the development of the primary internal position of a parent in primary school children; to describe the differences in the formation of components of the primary internal position of a parent in boys and girls. The study involved 85 children aged 8 to 9 years (39 boys and 46 girls). An experiment, creating the conditions for video games, content analysis of children’s statements, and projective and questionnaire methods were methodological tools of the study. The authors evaluated characteristics of drawings, statements and actions of children in the imaginary role of a parent. Most prominent criteria of the formation of the components of the internal position of a parent include the following: (a) the desire to have more than two children in the future; positive statements about the child, (b) use of support in emotionally significant situations, (c) use of endearment to a child. The obtained results also revealed a low level of the development of motivation (representation of the future family without children) and cognitive components of the internal position of a parent (formal statements about the child) in a significant number of junior schoolchildren.